Jews, Christians, and the discourse on images before iconoclasm - Sivertsev, Alexei (Cambridge University Press, 2024)
Explores the rise of image as a rhetorical category in Jewish and Christian literature originating between the sixth and eighth centuries. This book demonstrates how Jewish texts serve as an important witness to the formation of image discourse and associated practices of image veneration.